Evidence for Palaeozoic hydrothermal remobilization of fluorite mineralization in the Bushveld Igneous Complex, South Africa: insights from Sm-Nd geochronology and (isotope) geochemistry - Guillaume Jacques; Friedhelm Henjes-Kunst; Torsten Graupner; Zacharie Tardres; Guillaume Avice; Reiner Klemd (Journal of African Earth Sciences, 2026)

Preface: “Geodynamic evolution and metallogeny of the Hoggar massif” - Torsten Graupner; Abderrahmane Bendaoud; Mohamed Hamoudi; Astrid Holzheid; Basem Zoheir; El-Hocine Fettous; Simon Goldmann (Geochemistry, 2025)

Valorization of lithium containing slags from pyrometallurgical recycling route of spent lithium-ion batteries: The enrichment of γ-LiAlO2 phase from thermodynamic controlled and modified slags - Hao Qiu; Haojie Li; Michael Fischlschweiger; Marko Ranneberg; Torsten Graupner; Hugo Lucas; Christin Stallmeister; Bernd Friedrich; Bengi Yagmurlu; Daniel Goldmann (Minerals Engineering, 2024)

The In-Ga-Sb association of the post-Variscan Zn-Pb-Ag vein deposit at Lautenthal, Upper Harz Mountains, Germany: sphalerite mineral chemistry - Torsten Graupner; Sören Henning; Simon Goldmann; Sebastian Fuchs; Klaus Stedingk; Wilfried Liessmann; Sven Birkenfeld (Mineralium Deposita, 2024)
The Lautenthal sphalerite-galena vein deposit is part of the world-class Upper Harz Pb-Zn-Ag district in the Harz uplift block of the Paleozoic Variscan fold belt in Germany. Its sphalerite-dominated mineral association was studied using bulk-ore chemistry, electron probe microanalysis, and laser ablation-ICP-mass spectrometry. Gallium and locally In are the main high-tech-relevant trace elements hosted by sphalerite, with up to 150 ppm Ga and up to 380 ppm In in hand-picked sphalerite samples (mean In/Zn, 0.70 × 10 −3 ). Ore concentrates (≤ 50 kg) contain up to 65 ppm Ga and up to 109 ppm In (mean In/Zn, 0.36 × 10 −3 ). Accessory Fe-Co-rich gersdorffite-1 occurs in the earlier quartz-sulfide ore stage and Sb-rich gersdorffite-2 in the later carbonate-sulfide stage. Enrichment patterns of In are either defined by overprinting textures in the Fe-richer sphalerite-1 of the earlier stage, or relate to primary growth zoning in Fe-poor sphalerite-2 of the later stage. Using the sphalerite geothermometer GGIMFis, formation temperatures (median) of sphalerite-1 were estimated at ~ 230 °C for the Lautenthal orebody and at ~ 175 °C for the Bromberg orebody, which may indicate lateral T-zonation for the earlier ore stage. Sphalerite-2 data indicate formation temperatures of ~ 185 °C (median). Copper-bearing brines of the carbonate-sulfide stage with assumed temperatures of ~ 250 °C initiated replacement of In-poor sphalerite-1 by chalcopyrite and remobilization of Zn and trace elements. Indium-rich sphalerite-2 occurs associated with calcite and fine-grained galena. A direct spatial or temporal link of ore formation to a magmatic-hydrothermal system is unlikely, which contrasts to In-rich epithermal and tin-polymetallic vein deposits worldwide.

Magmatic evolution of the Schiel Alkaline Complex, Bushveld large igneous province, South Africa - Alica Höss; Reiner Klemd; Robert Bolhar; Karsten M. Haase; Joshua Ramos; Elena Geiger; Sönke Brandt; Torsten Graupner (Lithos, 2024)

Formation conditions and REY enrichment of the 2060 Ma phosphorus mineralization at Schiel (South Africa): geochemical and geochronological constraints - Torsten Graupner; Reiner Klemd; Friedhelm Henjes-Kunst; Simon Goldmann; Helge Behnsen; Axel Gerdes; Reiner Dohrmann; Jay M. Barton; Rehan Opperman (Mineralium Deposita, 2018)

Rock magnetic study of basic intrusions and massive sulphides in the Hercynian central Jebilets Massif (Occidental-Meseta), Morocco - Najib El Goumi; Mohammed Jaffal; Christian Rolf; Christoph Grissemann; Frank Melcher; Azzouz Kchikach; Mohammed Hibti; Torsten Graupner (Arabian Journal of Geosciences, 2013)

Geochemical Fingerprinting of Coltan Ores by Machine Learning on Uneven Datasets - Christian Savu-Krohn; Gerd Rantitsch; Peter Auer; Frank Melcher; Torsten Graupner (Natural Resources Research, 2011)

Multiple sources for mineralizing fluids in the Charmitan gold(-tungsten) mineralization (Uzbekistan) - Torsten Graupner; Samuel Niedermann; Dieter Rhede; Ulf Kempe; Reimar Seltmann; C. Terry Williams; Reiner Klemd (Mineralium Deposita, 2010)

The transition from porphyry- to epithermal-style gold mineralization at Ladolam, Lihir Island, Papua New Guinea: a reconnaissance study - Daniel Müller; Klaus Kaminski; Stephan Uhlig; Torsten Graupner; Peter M. Herzig; Steve Hunt (Mineralium Deposita, 2002)